CRISPR/Cas9 editing of CBP80 enhances drought tolerance in potato (Solanum tuberosum) - Décima Oneto, Cecilia Andrea (2025)
Developing drought-tolerant potato varieties is increasingly important due toclimate change and water scarcity, as potatoes are highly sensitive to waterdeficits that can significantly reduce yield and tuber quality. The cap-bindingprotein CBP80, involved in the abscisic acid (ABA) signalling pathway, hasemerged as a promising target for improving drought tolerance in plants. Inthis study, we used CRISPR/Cas9 to edit the StCBP80 gene in the tetraploidpotato cultivar Spunta. Given the complexity of editing all four alleles in atetraploid genome, eight independent partially edited lines (two or three allelesedited) were obtained. Two of these lines were selected for detailed molecularand phenotypic characterization. Under restricted water conditions, the selectedlines exhibited reduced transpiration rates and improved leaf area indexcompared to non-edited controls. Gene expression analysis by quantitativereal-time PCR showed differential expression of drought-responsive genes(P5CS, PDH, and MYB33), supporting a role for StCBP80 in stress responsemodulation. Moreover, the edited lines showed lower yield penalties, both inbiomass and tuber production, under drought stress. This work represents one ofthe first applications of genome editing to enhance drought tolerance in acommercial potato cultivar, and highlights CBP80 as a promising target forcrop improvement. These findings provide valuable insights for the developmentof stress-resilient potato varieties using genome editing approaches.